Legislating in hypertext - Wojciech Cyrul; Tomasz Pełech-Pilichowski (Opolskie Studia Administracyjno-Prawne, 2020)
Modern research on lawmaking in electronic format confirms the thesis that legal texts made available by means of various types of legal information systems form a hypertext structure. Furthermore, research on hypertexts confirms that the use of this technology undermines the structuralist theories of text that underlie traditional methods of legislation and interpretation of law. In this article, an attempt is made to show how a hypertext can be used to provide legal information and how it can affect traditional legal practices connected with drafting and interpreting legal texts. In particular, the considerations will focus on the analysis of the use of hypertext for the processing of legal documents (including digital representation of legal texts) and the possibilities that arise in this area in connection with the development of the so-called adaptive hypertexts. On this ground the question is analyzed whether and, if so, to what extent and in what way an adaptive hypertext can be used for the presentation and analysis of legal texts.